Acceding to the WTO from a Least-Developed Country Perspective - The Case of Ethiopia - Krajewski, Markus; Fikremarkos, Merso Birhanu (Nomos, 2011)
Acceding to the World Trade Organization (WTO) entails enormous challenges for developing countries, in particular least-developed ones such as the effects of market opening and international competition on the local economy as well as fundamental aspects of law and regulatory reform. The present volume addresses these questions from the perspective of Ethiopia, which is negotiating its accession to the WTO since 2003. Topics addressed include the effects of WTO law on agriculture, intellectual property rights and financial market regulation as well as regional integration in Africa. The book is not only of interest from the Ethiopian perspective, but will appeal to all interested in the impact of world trade law on developing countries